The Principal's Leadership Role in Creating a Student Literacy Culture - Kukuh Arif Prabowo; Ine Kusuma Aryani (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
Literacy is essential for students to enhance knowledge, comprehend learning materials, and engage in school activities through reading. It plays a crucial role in providing learning experiences and developing skills, preparing students for higher education and the workforce. Improving student literacy quality requires cooperation from all school members, with principals playing a key leadership role. Principals must effectively lead and collaborate with school communities to foster a literacy culture, enhancing students' literacy skills. This paper aims to describe and analyze the principal's leadership role in creating a student literacy culture. The study employs a literature review methodology, critically examining previous research and ideas. The process involves selecting discussion topics, sourcing literature, organizing materials, and reviewing findings, followed by writing. Data analysis is conducted using qualitative descriptive content analysis. The findings indicate that the principal's role includes being a policymaker, motivator, role model, and person in charge.